Evaluating the reality of the Islamic studies curriculum for the sixth grade of primary school in The Kingdom of Saudi Arabia in the light of pragmatic theory - Al-Wadany, Felwah Mohmmad Saqar (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to evaluate the Islamic education curriculum for the sixth grade in the Kingdom of Saudi Arabia in the light of the theory of the pragmatic approach, and to reveal the degree of availability of the principles and indicators of the pragmatic theory in the Islamic studies course in the sixth grade of primary school. For the sixth grade of primary school scheduled in government schools for the academic year 1444 AH/ 2022 AD, by building a content analysis card in the light of the principles of the pragmatic curriculum theory. Significant, and in the light of the results of the study, the researcher recommended the need to pay attention to the preparation of projects and extracurricular activities as a method of evaluation in the Islamic education curriculum.